روحانية مكان العمل ودورها في مواجهة السلوكيات القيادية التدميرية دراسة حالة في مستشفى الاسكندرية العام - العبيدي, عصام عليوي صاحب (Sulaimani Journal for Humanities, 2025)
The purpose of this research is to investigate the relationship between workplace spirituality and destructive leadership behaviors in Alexandria General Hospital importance of research includes rare of studies that investigated the relationship between workplace spirituality and destructive leadership behaviors. Furthermore, there is a reality problem, which has a significant effect on Iraqi Health Sector. Based on the random sampling, 162 questionnaires were distributed to employees at Alexandria General Hospital. Only 157 questionnaires were returned. Out of which 154 questionnaires were usable resulting into a response rate of 98%. The theoretical results show the knowledge gap related to identification the nature of the relationship between workplace spirituality and destructive leadership behaviors. Moreover, the practical results show the significant and Reverse of workplace spirituality on destructive leadership behaviors.